Financial Problems of the Multi-National Corporation: Discussion - Bennett, J. F. (Journal of Finance, 1966)
J. F. Bennett, Financial Problems of the Multi-National Corporation: Discussion, The Journal of Finance, Vol. 21, No. 2, Papers and Proceedings of the Twenty-Fourth Annual Meeting of the American Finance Association, New York, New York, December 28-30, 1965 (May, 1966), pp. 308-310